Metalloproteinases and their Inhibitors under the Course of Immunostimulation by CPG-ODN and Specific Antigen Inhalation in Equine Asthma - Ann Kristin Barton; Tarek Shety; John Klier; Sabine Geis; Ralf Einspanier; Heidrun Gehlen (Mediators of Inflammation)
Objectives. Inhalation of immunostimulatory bacterial DNA segments (cytosine-phosphate-guanosine-oligodeoxynucleotides, CpG-ODN) normalizes clinical and cytologic parameters in severe equine asthma. We hypothesized that CpG-ODN inhalation also reduces the misbalance of elastinolytic activity in asthmatic horses. Methods. Twenty asthmatic horses diagnosed by clinical examinations using a scoring system were included. All horses inhaled CpG-ODNs for 14 days in 2-day intervals. Matrix metalloproteinase (MMP-2/-9) and tissue inhibitors of metalloproteinase (TIMP-1/-2) concentrations were measured in tracheal aspirates using equine sandwich ELISAs before and 2 and 6 weeks after CpG-ODN inhalation. Results. MMP and TIMP concentrations correlated with the results of clinical scoring in all stages of equine asthma. Inhalation therapy led to significant reductions in clinical scores. MMP-2, MMP-9, and TIMP-2 concentrations were significantly reduced immediately, and all MMP and TIMP concentrations 6 weeks after therapy. Discussion. In equine asthma, overexpression of MMPs contributes to pathological tissue destruction, while TIMPs counteract MMPs with overexpression leading to fibrosis formation. The results of this study show that CpG-ODN inhalation may be an effective therapy to address a misbalance in equine asthma. Conclusions. Misbalance of elastinolytic activity seems to improve by CpG-ODN inhalation for at least 6 weeks posttherapy, which may reduce the remodeling of the extracellular matrix. Further studies should evaluate this effect in comparison to glucocorticoid inhalation therapy. Significance. CpG-ODN inhalation may be an effective therapy in the prevention of pulmonary fibrosis formation in equine asthma.